2014
DOI: 10.1111/epi.12545
|View full text |Cite
|
Sign up to set email alerts
|

Developmental brain abnormalities in tuberous sclerosis complex: A comparative tissue analysis of cortical tubers and perituberal cortex

Abstract: SUMMARYObjective: Genetic loss of Tsc1/Tsc2 function in tuberous sclerosis complex (TSC) results in altered mammalian target of rapamycin (mTOR) signaling and abnormal brain development. Although earlier studies have focused on characterization of cortical tubers, in this study we sought to examine the unique cellular and molecular features of the perituberal cortex in order to better understand its contribution to epileptogenesis, cognitive dysfunction, and autism. Methods: Standard histologic and immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 73 publications
7
77
0
3
Order By: Relevance
“…Furthermore, several studies using MRI diffusion techniques revealed diffuse alterations in the so-called normally appearing WM [3,4], but the relation between WM alterations and neurologic phenotype remains to be clarified. WM alterations seen by MRI studies are in good agreement with diffuse microstructural WM abnormalities found in neuropathological studies in individuals with TSC, reflecting axonal disorganization, reduced/altered myelination, or gliosis [5][6][7]. WM alterations might result from the dysregulation of the mTOR pathway, which is responsible for abnormal connectivity as well as for altered axonal growth [8][9][10].…”
Section: Introductionsupporting
confidence: 79%
“…Furthermore, several studies using MRI diffusion techniques revealed diffuse alterations in the so-called normally appearing WM [3,4], but the relation between WM alterations and neurologic phenotype remains to be clarified. WM alterations seen by MRI studies are in good agreement with diffuse microstructural WM abnormalities found in neuropathological studies in individuals with TSC, reflecting axonal disorganization, reduced/altered myelination, or gliosis [5][6][7]. WM alterations might result from the dysregulation of the mTOR pathway, which is responsible for abnormal connectivity as well as for altered axonal growth [8][9][10].…”
Section: Introductionsupporting
confidence: 79%
“…7 AD changes are caused by axonal and functional changes, 7 suggesting that our observed increases in AD within epileptogenic perituberal tissue may result from increased axonal connectivity and growth. 3 The coexistence of both AD and RD changes have resulted in no substantial anisotropy changes, as indicated by our findings of no FA difference between epileptogenic and nonepileptogenic tubers. This result conflicts with previous studies reporting significantly lower FA values in epileptogenic tubers or in normal-appearing white matter adjacent to epileptogenic tubers compared with nonepileptogenic areas.…”
Section: Resultsmentioning
confidence: 54%
“…Histopathologically, tubers show the presence of dysplastic neurons and giant cells, increased axonal connectivity, and hypomyelination. 3 Perituberal cortex also demonstrates similar histologic features. 3 Our results are therefore consistent with these histopathologic changes since dysplastic neurons and astrogliosis may result in increased ADC.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations